Extracellular Vesicles as Mediators of Cellular Cross Talk in the Lung Microenvironment - Bartel, Sabine; Deshane, Jessy; Wilkinson, Tom; Gabrielsson, Susanne (Frontiers in Medicine, 2020)
The human lung is a complex tissue subdivided into several regions that differ in size, function and resident cell types. Despite years of intensive research, we still do not fully understand the crosstalk between these different regions and diverse cell populations in the lung and how this is altered in the development of chronic respiratory disease. The discovery of extracellular vesicles (EV), small membrane vesicles released from cells for inter-cellular communication, has added another layer of complexity to cellular crosstalk in the complex lung microenvironment. EVs from patients with COPD, asthma or sarcoidosis have been shown to carry miRNAs, proteins and lipids which may contribute to inflammation or tissue degeneration. Here, we summarize the contribution of these small vesicles in the interplay of several different cell types in the lung microenvironment, with a focus on the development of chronic respiratory diseases. While there are already many studies demonstrating negative effects of EVs in the diseased lung, we still have substantial knowledge gaps regarding the concrete role of EV involvement in lung disease that should be addressed in future studies.